Zoogeografía y ecología de los peces de aguas continentales de la Argentina y consideraciones sobre las áreas ictiológicas de América del Sur - Ringuelet, Raúl A. (Ecosur, 2025)
This study comprises a critical review of relevant literature on the fish fauna, genocentres, means of dispersal, barriers, ecological groups, coactions, and ecological causality of distribution, including an analysis of allotopic species in the same lake or pond, the application of indexes of diversity of several biotopes and comments on historical factors. Its wide scope allows to clarify several aspects of South American Ichthyogeography. The location of Argentina ichthyological fauna according to the abovemencioned distributional scheme as well as its relation with the most important hydrography Systems are also provided, followed by additional information on its distribution in the Argentine Republic, including an analysis through the application of Simpson’s similitude test in several localities.